Nocturia in patients with benign prostatic hyperplasia: evaluating the significance of ageing, co-morbid illnesses, lifestyle and medical therapy in treatment outcome in real life practice. (June 2015) - Singam, Praveen; Hong, Goh Eng; Ho, Christopher; Hee, Tan Guan; Jasman, Hafidzul; Inn, Fam Xeng; Bahadzor, Badrulhisham; Tamil, Azmi; Zainuddin, Zulkifli
Abstract Aim: The aim of study was to evaluate the influence of ageing, lifestyle, and co morbid illnesses on treatment outcome of nocturia among men with BPH. Methods: Patients with BPH on medical therapy of least 6 months and up to 48 months were interviewed. Nocturia episodes, co morbid illnesses, beverage intake frequency, medications and work history were documented. Body Mass Index (BMI), waist circumference (WC), prostate volume, and prostate specific antigen (PSA) were recorded. Treatment failure is defined as persistent nocturia despite on medical therapy for BPH. Results: In 156 patients, the prevalence of nocturia was 96.7% while nocturia of 2 or more was 85.9%. Factors associated with treatment failure was older age (p < 0.01), usage of diuretics (p = 0.03), and antimuscarinics (p < 0.01), while active working status (p < 0.01), use of desmopression (p = 0.01), and increased coffee intake (p = 0.02) were associated with nocturia improvement. Co-morbid illnesses, obesity, WC, alcohol intake, PSA, prostate volume, and use of BPH medical therapy did not influence treatment outcome. Conclusion: Advancing age has a significance negative outcome on nocturia treatment, while standard BPH medical therapy and co morbid illnesses have an insignificant impact. However, alleviation of bothersome symptoms is possible with the understanding of its patho-physiology and individual-based approach to treatment and expected outcome.